Constitutive IRAK4 Activation Underlies Poor Prognosis and Chemoresistance In Pancreatic Ductal Adenocarcinoma - Zhang, Daoxiang (Clin Cancer Res, 2016)
PURPOSE: Aberrant activation of the NF-κB transcription factors underlies the aggressive behavior and poor outcome of pancreatic ductal adenocarcinoma (PDAC). However, clinically effective and safe NF-κB inhibitors are not yet available. Because NF-κB transcription factors can be activated by the Interleukin-1 Receptor-Associated Kinase (IRAK) downstream of the Toll-like receptors (TLRs), but has not been explored in PDAC, we sought to investigate the role of IRAK in the pathobiology of PDAC. EXPERIMENTAL DESIGN: We examined the phosphorylation status of IRAK4 (p-IRAK4), the master regulator of TLR signaling, in PDAC cell lines, in surgical samples and commercial tissue microarray. We then performed functional studies using small molecule IRAK1/4 inhibitor, RNA-interference and CRISPR/Cas9n techniques to delineate the role of IRAK4 in NF-κB activity, chemoresistance, cytokine production and growth of PDAC cells in vitro and in vivo. RESULTS: p-IRAK4 staining was detectable in the majority of PDAC lines and about 60% of human PDAC samples. Presence of p-IRAK4 strongly correlated with phospho-NF-κB/p65 staining in PDAC samples and is predictive of postoperative relapse and poor overall survival. Inhibition of IRAK4 potently reduced NF-κB activity, anchorage-independent growth, chemoresistance and secretion of pro-inflammatory cytokines from PDAC cells. Both pharmacologic suppression and genetic ablation of IRAK4 greatly abolished PDAC growth in mice and augmented the therapeutic effect of gemcitabine by promoting apoptosis, reducing tumor cell proliferation and tumor fibrosis. CONCLUSIONS: Our data established IRAK4 as a novel therapeutic target for PDAC treatment. Development of potent IRAK4 inhibitors is needed for clinical testing.